A study on heat transfer enhancement of Copper (Cu)-Ethylene glycol based nanoparticle on radial stretching sheet - Iqbal, Azhar; Abbas, Tasawar (Alexandria engineering journal, 2023)
Copper nanoparticles are getting attention because of their outstanding physical characteristics and wide range of uses. The motivation of this research is to investigate axisymmetric flow and heat transfer for various shapes (Cylinder, Platelets and Sphere) of Copper (Cu) nanoparticles on a radial stretching sheet. Energy and momentum partial differential equations are transformed into nonlinear ordinary differential equations (ODE). The dimensionless equations are solved using the BVP4C method to yield numerical solutions for the represented problem. The impacts of multi-shape Copper (Cu) nanoparticles are thoroughly examined, as are other parameters such as solid volume fraction (ϕ), Prandtl number Pr, unsteadiness parameter S, magnetic parameter M, slip parameter k, and Eckert number EC. According to the findings, Platelet shape Copper (Cu) nanoparticles have the highest flow and Sphere shape particles contain maximum heat transfer rate.